HUBUNGAN BERAT BADAN DAN TINGGI BADAN TERHADAP KECEPATAN RENANG GAYA BEBAS 50 METER PADA ATLET BULAKAN AQUATIC CLUB BATANG TABIK KABUPATEN LIMA PULUH KOTA - Mhd Adam Alfatoni; Pringgo Mardesia; Yogi Arnaldo Putra; Anisa Sholiha Mia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the relationship between body weight and body height on 50-meter freestyle swimming speed among Bulakan Aquatic Club athletes. This research employed a quantitative correlational design. The population consisted of 10 athletes and all were selected as samples through total sampling. Data collection was conducted using digital scales, stadiometer measurements, and a 50-meter freestyle swimming test. Data analysis included descriptive statistics, Shapiro-Wilk normality test, Pearson Product Moment correlation, coefficient of determination, multiple correlation, and F-test. The results indicated a significant relationship between body weight and freestyle swimming speed (r = -0.637; p = 0.048) with a contribution of 40.6%. Body height also showed a significant relationship with freestyle swimming speed (r = -0.680; p = 0.031) with a contribution of 46.24%. Simultaneously, body weight and body height produced R = 0.680 and R² = 0.462. However, the F-test yielded a significance value of 0.114 (p > 0.05), indicating no statistically significant relationship simultaneously. Therefore, body weight and body height have significant partial relationships but not a significant simultaneous relationship with 50-meter freestyle swimming speed.